COT-TT vaccine attenuates induction and expression of cocaine-induced behavioral sensitization in rats: a dose-response study - Barbosa-Mendez, Sasana; Salazar-Juárez, Alberto (Frontiers in Psychiatry, 2025)
IntroductionActive vaccination is an effective therapeutic strategy, capable of decreasing the reinforcing and psychomotor effects of cocaine. Clinical studies have shown that cocaine vaccines show an irregular generation of antibody titers, which are rapidly reduced in the absence of reimmunization. The COC-TT vaccine has demonstrated, in rodents, the production of high levels of anti-cocaine antibodies, capable of reducing the cocaine-reinforcing effects, but the adequate dose to obtain the highest antibody titers has not yet been determined, as well as the kinetics of the decay of titers and the capacity to decrease the locomotor activity induced by different doses of cocaine during the phase of decay of titers, induction and expression of locomotor sensitization. The objective of this study was to determine the optimal dose of the COC-TT vaccine, the decay kinetics of anti-cocaine titers, and the efficacy of the antibodies to decrease the locomotor activity induced by different doses of cocaine.MethodsMale Wistar rats were immunized with the COC-TT. A solid-phase antibody-capture ELISA was used to monitor antibody titer responses after each booster dose in vaccinated animals. The study used cocaine-induced locomotor activity testing to evaluate the cocaine-psychomotor effects.ResultsThe COC-TT vaccine could generate high levels of anti-cocaine antibodies. These showed a gradual, dose-dependent decay kinetics of the COC-TT vaccine and a rapid recovery in antibody levels after re-immunization. Furthermore, the antibodies attenuated cocaine-induced locomotor activity during the induction and expression of locomotor sensitization.DiscussionThese findings suggest that the COC-TT vaccine generates a robust immunogenic response capable of reducing the reinforcing effects of cocaine, which supports its possible future use in clinical trials in patients with CUD.